Gender and Cultural Conditioning of Victorian Small Talk - Морозова, Ірина Ігорівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
This paper focuses on the influence exercised by the gender and social and cultural factors over women’s speech in the communicative situation of small talk, one of the main situations of the Victorian female discourse. The following structural elements are found to be constant in terms of their cultural dependence: language (standard English of the mid-to-late 19th century), communication mode (everyday discourse), addresser (a female representative of the upper / middle classes), aim (establishing and maintaining contact), tone (neutral) and place (social events). It is proved that the small talk topics arrangement – weather, travelling, arts, literature, food, household items, etc. – depends on the type of communication, a mono- or a cross-gender one. The topics of stylish entertainment, pastimes and health are characteristic of the former and entertainment, pastimes and arts are typical for the latter while “the weather” and “clothes” are mentioned by the Victorian woman least of all in the corresponding communicative situations. Another feature stipulated by the character of the situation under study is the component of only secondary social groups in its symmetrical and asymmetrical variants where the woman has a role of a socialite. On the whole, the communicative situation under consideration is aimed at implementing a positive politeness strategy of “Presuppose, raise, assert common ground” and establishing a community of interacting individuals. The strategy is explicated in the woman’s speech with the help of vocabulary and syntactical units (including formulaic expressions) that denote discussed subjects.